Sphingomonas baiyangensis sp. nov., isolated from water in Baiyang Lake. Issue 9 (29th September 2022) - Wei, Da-Wei; Yang, Yunzhen; Zeng, Yuan; Wang, Chao; Feng, Jie
Abstract : A novel Gram-stain-negative, short-rod-shaped, orange-pigmented bacterial strain, designated L-1–4 w-11 T, was isolated from Baiyang Lake in China. The strain grew at 15–35 °C (optimum 30 °C) and pH 7–8 (optimum pH 7) in TSA medium. The predominant polar lipids of strain L-1–4 w-11 T were sphingoglycolipid, phosphatidylethanolamine, phosphatidylcholine, phosphatidylglycerol, diphosphatidylglycerol, one unidentified glycolipid and three unidentified lipids; the major cellular fatty acids were C17 : 1 ω6 c and summed feature 8 (C18 : 1 ω7 c and/or C18 : 1 ω6 c ); and the major respiratory quinone was ubiquinone 10 (Q-10). Strain L-1–4 w-11 T showed the highest 16S rRNA gene sequence similarity to Sphingomonas japonica JCM 15438 T (98.3 %) and S. spermidinifaciens GDMCC 1.657 T (98.0 %). The draft genome size of strain L-1–4 w-11 T was 3.3 Mbp, and the G+C content was 67.8 mol%. Digital DNA–DNA hydridization and average nucleotide identity values between the genome sequences of strain L-1–4 w-11 T and S. spermidinifaciens GDMCC 1.657 T (76.9 and 21.0 %), S. japonica JCM 15438 T (76.0 and 19.9 %) and S. paucimobilis CGMCC 1.12825 T (72.8 and 19.6 %) were far below the thresholds for prokaryotic conspecific assignment. With the evidence from the phylogenetic, chemotaxonomic and genotypic analyses, we propose that strain L-1–4 w-11 T represents a novel Sphingomonas species with the name S. baiyangensis sp. nov. The type strain is L-1–4 w-11 T (=CGMCC 1.13572 T =JCM 33962 T ).